Experimental study on the mechanical behavior and deformation characteristics of lining structure of super-large section tunnels with a small clearance. (June 2022) - Zhang, Heng; Zhang, Gang; Pan, Yingdong; Hao, Zihan; Chen, Shougen; Cheng, Fanghui
Highlights: The destructive test under different clearances of twin tunnels was conducted. The deformation and failure characteristics of secondary linings were revealed. The ultimate bearing load and the radial displacements were analyzed. The internal force of the secondary linings when the failure occurred was obtained. Abstract: The knowledge of the mechanical behavior and deformation characteristics of lining structure of super-large section tunnels with a small clearance can help to optimize the tunnel lining design and reduce the construction costs. Based on Xinwu twin tunnels with eight lanes in China, a reduced-scale model experiment was carried out to investigate the deformation characteristics, the crack behaviors, the ultimate bearing load and internal force of the super-large section tunnels under different clearances. The results show that the positions in order (from largest to smallest deformation) are as follows: crown, right spandrel, left spandrel, invert, springs. 12 m (about half the width of tunnel) can be considered as the smallest reasonable spacing for large section tunnels in grade IV surrounding rock. With the increase of loading level, the cracks mainly appeared at the invert and the springs of the two tunnels. After the secondary lining was damaged, the deformation of each measuring point did not decrease but gradually increased with the clearance. These findings can provide significant reference data for the design optimization and safety assessment of super-large section tunnels with a small clearance.